2021
DOI: 10.3389/fimmu.2021.715209
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Exposure to Peritoneal Dialysis Fluid Alters Resident Peritoneal Macrophage Phenotype and Activation Propensity

Abstract: Peritoneal dialysis (PD) is a more continuous alternative to haemodialysis, for patients with chronic kidney disease, with considerable initial benefits for survival, patient independence and healthcare costs. However, long-term PD is associated with significant pathology, negating the positive effects over haemodialysis. Importantly, peritonitis and activation of macrophages is closely associated with disease progression and treatment failure. However, recent advances in macrophage biology suggest opposite fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…15 Moreover, the macrophages have been reported to play a pivotal role in the progression of peritoneal deterioration. 14,32,33 Macrophages are likely to remain in peritoneal tissue after the onset of PD-related acute peritonitis. Notably, it has been reported that significance changes of the prevalence of macrophage/monocyte populations varies widely in PD patients, depending on the history of peritonitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Moreover, the macrophages have been reported to play a pivotal role in the progression of peritoneal deterioration. 14,32,33 Macrophages are likely to remain in peritoneal tissue after the onset of PD-related acute peritonitis. Notably, it has been reported that significance changes of the prevalence of macrophage/monocyte populations varies widely in PD patients, depending on the history of peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 inflammasome‐induced PD‐related acute peritonitis has been suggested to occur predominantly in the resident peritoneal monocytes and macrophages 15 . Moreover, the macrophages have been reported to play a pivotal role in the progression of peritoneal deterioration 14,32,33 . Macrophages are likely to remain in peritoneal tissue after the onset of PD‐related acute peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this effect is that long-term PD may affect the peritoneum, as Tara et al. [ 21 ] suggested. Alterations in tissue-resident macrophages could render long-term PD patients more susceptible to developing peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that chronic exposure to PDFs alters resident MØs homeostatic phenotype, including the lost expression of anti-inflammatory and efferocytosis markers and enhanced inflammatory response [ 57 ]. Another study demonstrated the role of M1 instead of M2 MØs in peritoneal damage by depleting and transplanting different MØs populations into PDF-exposed mice [ 58 ].…”
Section: Cellular and Molecular Mechanisms Implicated In The Damage O...mentioning
confidence: 99%